Active lifestyles moderate clinical outcomes in autosomal dominant frontotemporal degeneration. Issue 1 (8th January 2020) - Casaletto, K. B.; Staffaroni, A. M.; Wolf, A.; Appleby, B.; Brushaber, D.; Coppola, G.; Dickerson, B.; Domoto‐Reilly, K.; Elahi, F. M.; Fields, J.; Fong, J. C.; Forsberg, L.; et al.
Abstract: Introduction: Leisure activities impact brain aging and may be prevention targets. We characterized how physical and cognitive activities relate to brain health for the first time in autosomal dominant frontotemporal lobar degeneration (FTLD). Methods: A total of 105 mutation carriers ( C9orf72/MAPT/GRN ) and 69 non‐carriers reported current physical and cognitive activities at baseline, and completed longitudinal neurobehavioral assessments and brain magnetic resonance imaging (MRI) scans. Results: Greater physical and cognitive activities were each associated with an estimated >55% slower clinical decline per year among dominant gene carriers. There was also an interaction between leisure activities and frontotemporal atrophy on cognition in mutation carriers. High‐activity carriers with frontotemporal atrophy (−1 standard deviation/year) demonstrated >two‐fold better cognitive performances per year compared to their less active peers with comparable atrophy rates. Discussion: Active lifestyles were associated with less functional decline and moderated brain‐to‐behavior relationships longitudinally. More active carriers "outperformed" brain volume, commensurate with a cognitive reserve hypothesis. Lifestyle may confer clinical resilience, even in autosomal dominant FTLD.